Impaired hypoxic sensor Siah‐1, PHD3, and FIH system in spinal motor neurons of an amyotrophic lateral sclerosis mouse model. Issue 2 (14th November 2012) - Sato, Kota; Morimoto, Nobutoshi; Kurata, Tomoko; Mimoto, Takafumi; Miyazaki, Kazunori; Ikeda, Yoshio; Abe, Koji
Abstract We recently reported spinal blood flow–metabolism uncoupling in the Cu/Zn‐superoxide dismutase 1 (SOD1)‐transgenic (Tg) mouse model of amyotrophic lateral sclerosis (ALS), suggesting relative hypoxia in the spinal cord. However, the hypoxic stress sensor pathway in ALS has not been well studied. In the present work, we examined the temporal and spatial changes of hypoxic stress sensor proteins (Siah‐1, PHD3, and FIH) following motor neuron (MN) degeneration in the spinal cord of normoxic ALS mice. The expression of Siah‐1 and PHD3 proteins progressively increased in the surrounding glial cells of presymptomatic Tg mice (10 weeks, 10 weeks) compared with the large MN of the anterior horn. In contrast, a significant reduction in Siah‐1 and PHD3 protein expression was evident in end‐stage ALS mice (18 weeks, 18 weeks). Double‐immunofluorescence analysis revealed PHD3 plus Siah‐1 double‐positive cells in the surrounding glia of symptomatic Tg mice (14–18 weeks), with no change in the large MNs. In contrast, FIH protein expression decreased in the surrounding glial cells of Tg mice at end‐stage ALS (18 weeks). The present study suggests a partial loss in the neuroprotective response of spinal MNs in ALS results from a relative hypoxia through the Siah‐1, PHD3, and FIH system under normoxic conditions. This response could be an important mechanism of neurodegeneration in ALS. © 2012 Wiley Periodicals, Inc.